2017
DOI: 10.1002/app.45768
|View full text |Cite
|
Sign up to set email alerts
|

Glass fiber reinforced and β‐nucleating agents regulated polypropylene: A complementary approach and a case study

Abstract: A two-step process for preparing glass fibers (GFs) reinforced b-nucleated PP composites was designed and developed. The complementary approach combined GFs reinforcement and b-nucleating agents regulation using N,N 0 -dicyclohexyl-2,6-napthalenedicarboxamide (TMB-5) in the presence of maleic anhydride grafted polypropylene (PP-g-MA) through extrusion blending. The influence of TMB-5 and GFs on the mechanical properties and crystallization behavior of PP was studied by mechanical test, wide-angle Xray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The diverse aggregation structure of aromatic amide NA not only showed different β‐nucleating selectivity and nucleation efficiency, but also could induce iPP to crystallize into various crystallization morphologies, such as β‐spherulites, β‐transcrystalline and β‐“flower”‐like agglomerates, which in turn affected the macroscopic properties of the material . Numerous researches have been dedicated to study the effects of NA agglomerates on the properties of iPP, such as mechanical, charge storage, and barrier performances . Those work were very meaningful to regulate the properties of the product by tuning the NA morphology, but this is not the focus in this review.…”
Section: The Effects Of Diverse Agglomerates On β‐Nucleation Ability mentioning
confidence: 99%
“…The diverse aggregation structure of aromatic amide NA not only showed different β‐nucleating selectivity and nucleation efficiency, but also could induce iPP to crystallize into various crystallization morphologies, such as β‐spherulites, β‐transcrystalline and β‐“flower”‐like agglomerates, which in turn affected the macroscopic properties of the material . Numerous researches have been dedicated to study the effects of NA agglomerates on the properties of iPP, such as mechanical, charge storage, and barrier performances . Those work were very meaningful to regulate the properties of the product by tuning the NA morphology, but this is not the focus in this review.…”
Section: The Effects Of Diverse Agglomerates On β‐Nucleation Ability mentioning
confidence: 99%
“…For PP‐β and PP/CF(10%)‐β samples, they showed abundant β‐crystals with smaller size and higher birefringent than α‐crystals, typical grain refinement phenomenon were observed. It suggested that the PA‐01 was an effective β‐nucleating agent to generate abundant β‐crystals in PP matrix …”
Section: Resultsmentioning
confidence: 99%
“…Despite this problem, DCHT has been used in several other studies, both before [22,23] and after [24][25][26][27][28][29][30][31] the discoveries of Varga and Menyhárd, including studies of processing effects [32]. Quite recently, combined effects of DCHT nucleation and glass fiber (GF) reinforcement have been studied [33], finding a better performance than in combination of GF and α-nucleation [34]. This combination has, however, already been shown to be effective before, mostly because of an interlayer formation around the fiber [35,36].…”
Section: Introductionmentioning
confidence: 99%